The Crock of Gold: A Rural Novel - Tupper, Martin Farquhar, 1810-1889 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Crock of Gold: A Rural Novel" by Martin Farquhar Tupper is a fictional work written in the mid-19th century. The narrative centers around Roger Acton, a laborer dealing with the harsh realities of poverty, discontent, and the lure of wealth in a rural setting. Tupper explores themes of socio-economic disparity, moral struggle, and the impact of greed on the human spirit, presenting a poignant portrayal of the rural working class. The opening of the novel introduces Roger Acton, who awakens before dawn in bleak and cold conditions, emphasizing his toil as a laborer and the discontent that has begun to fester within him. As he prepares for a day of hard work, we learn about his life and the burdens he carries, including the losses he has endured and the hardships that plague his family. With his daughter Grace often reading him verses from the Bible to uplift his spirits, Roger's internal conflict escalates as he fantasizes about a "crock of gold." His discontent grows ever deeper as challenges mount, prompting him to contemplate the morality of his desires and the nature of his existence within a society that seems to favor the wealthy. Thus, the stage is set for a narrative that grapples with the complexities of human experience against the backdrop of rural life. (This is an automatically generated summary.)
Release date is 2005-11-14
E-text prepared by Jonathan Ingram, Janet Blenkinship, and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net/)
Keywords: Fiction